Recent advances and prospects in the organocatalytic synthesis of quinazolinones - Borah, Biplob; Swain, Sidhartha; Patat, Mihir; Chowhan, L. Raju (Frontiers in Chemistry, 2022)
Quinazolinone, a bicyclic compound comprises a pyrimidine ring fused at 4´ and 8´ positions with a benzene ring constitutes a substantial class of nitrogen-containing heterocyclic compounds on account of their frequent existence in the key fragments of many natural alkaloids and pharmaceutically active components. Consequently, tremendous efforts have been subjected to the elegant construction of these compounds and have recently received immense interest in synthetic and medicinal chemistry. The domain of synthetic organic chemistry has grown significantly over the past few decades for the construction of highly functionalized therapeutically potential complex molecular structures with the aid of small organic molecules by replacing transition-metal catalysis. The rapid access to this heterocycle by means of organocatalytic strategy has provided new alternatives from the viewpoint of synthetic and green chemistry. In this review article, we have demonstrated a clear presentation of the recent organocatalytic synthesis of quinazolinones of potential therapeutic interests and covered the literature from 2015 to date. Besides these, a clear presentation and understanding of the mechanistic aspects, features, and limitations of the developed reaction methodologies, have been highlighted.